Proyecto de inversión para la creación de una empresa de comercialización y producción de ropa para el adulto mayor en la ciudad de Pereira Risaralda (2013)
This paper work had as objective to identify the needs of the elderly in terms of garments, in order to analyze the real conditions of putting in place a marketing and production facility where be offered all kind of alternatives and variations of exclusive garments and with excellent quality for the elderly. To accomplish this goal was made a type of descriptive study with a deductive method using tools such as survey and interview that helped to determine their different tastes, preferences and needs. Subsequent to the completion of a market study and taking into account the acceptance of the product to the target population, the technical study was performed to determine the more convenient size of the project, and the final location of the same, which is conditional on a number relevant aspects such as: facility adjustments, transportation, media, public services, which are important to making decisions regarding the viability of the project, was created the legal and administrative study that allows to collect information necessary to establish the way to legalize the business, and describes other aspects such as: name, objectives, policies, activities proper to fulfill the mission and vision, the organization form, patrimonial composition and others derived from the complexity of the organization. Finally ran the financial study that records each of the elements involved in the financial structuring of the project such as: the investment required to operate it, the costs which contribute to the marketing of each of the products or services offered by the company, all this information projected on each of the periods that compromises the project horizon.